¿Qué escribir en la escuela? Análisis de una propuesta institucional de escritura a través del currículum - Federico Navarro (Universitat Autònoma de Barcelona, 2013)
This article aims to contribute to the teaching of reading and writing. It provides a description of the Writing Program at School, a project that critically adapts the writing across the curriculum perspective in the initial and advanced courses of a high school in Buenos Aires (Argentina), and that can be replicated in other educational settings. The course is run by a writing teacher that cooperates with a different subject teacher every trimester in a two-way training process. Both general and discipline-specific literacy abilities are focused through creative and regulated text rewriting: basic writing skills, metacognitive skills, school genres, ICTs, and style. Preliminary results show a positive impact of the program both on participating students and teachers.